Unprecedented Alkene Transposition in Phthalate–Amino Acid Adducts - Saha, Ishika; Baxendale, Ian R.; Baumann, Marcus (Synlett, 2018)
A detailed account on the outcome of the thermal reaction between benzylidene phthalides and various amino acid derivatives is reported. It was discovered that the tricyclic pyrroles as previously described are not the products formed in these reactions. Instead under high-temperature conditions decarboxylated phthalamide adducts are formed within 5-10 minutes. Additionally, an unprecedented alkene transposition mechanism has been identified leading to the final products of these reactions.
Keywords: phthalide; phthalamide; tricyclic pyrrole; alkene transposition